2001
DOI: 10.1128/aem.67.1.260-269.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role for Outer Membrane Cytochromes OmcA and OmcB of Shewanella putrefaciens MR-1 in Reduction of Manganese Dioxide

Abstract: Shewanella putrefaciens MR-1 can use a wide variety of terminal electron acceptors for anaerobic respiration, including certain insoluble manganese and iron oxides. To examine whether the outer membrane (OM) cytochromes of MR-1 play a role in Mn(IV) and Fe(III) reduction, mutants lacking the OM cytochrome OmcA or OmcB were isolated by gene replacement. Southern blotting and PCR confirmed replacement of the omcA and omcB genes, respectively, and reverse transcription-PCR analysis demonstrated loss of the respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
206
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(224 citation statements)
references
References 42 publications
18
206
0
Order By: Relevance
“…These include OmcA and OmcB, which are known to be involved in the reduction of extracellular MnO 2 (ref. 16). Diversification of the S. oneidensis decaheme cytochrome c proteins has allowed for a specialization of labor of these proteins in both cellular location (i.e., the periplasmic side of the cytoplasmic membrane, the periplasmic space, and the outer membrane) and specific electron-transporting role.…”
Section: Online)mentioning
confidence: 99%
“…These include OmcA and OmcB, which are known to be involved in the reduction of extracellular MnO 2 (ref. 16). Diversification of the S. oneidensis decaheme cytochrome c proteins has allowed for a specialization of labor of these proteins in both cellular location (i.e., the periplasmic side of the cytoplasmic membrane, the periplasmic space, and the outer membrane) and specific electron-transporting role.…”
Section: Online)mentioning
confidence: 99%
“…Electron transport proteins proposed to be involved in Fe(III) respiration in Shewanella oneidensis MR-1 include an inner-membrane periplasmic tetraheme quinol dehydrogenase (CymA) [8,12], two periplasmic decaheme cytochromes (MtrD and MtrA) [10,13], periplasmic tetraheme cytochrome (Stc) [14,15], the cytochrome domain of Fe(III)-induced flavocytochrome c 3 , [16] two putative outer-membrane b-barrel proteins (MtrE and MtrB) [17][18][19] and three outer-membrane decaheme cytochromes (MtrF, OmcA and MtrC) [11,18,20,21]. Although genetic studies have identified specific proteins that are involved in Fe(III) respiration in Shewanella sp.…”
Section: Introductionmentioning
confidence: 99%
“…OmcA and MtrC protein sequences both comprise ten putative cheme binding site motifs (CXXCH, where X is any residue) and a lipid-binding motif for anchoring to the outer membrane [11,22]. Because of their proposed location, these multiheme cytochromes are believed to function in Fe(III) respiration by mediating electron transfer across the microbe-mineral oxidant interface [5,10,13,18,22]. Significantly, a DmtrC strain of S. oneidensis MR-1 displayed a marked decrease in the ability to respire iron(III) oxides and iron(III) citrate, while retaining the ability to respire soluble terminal electron acceptors, including NO 3 À and NO 2 À [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the specific mechanism of Ni(II) reduction in strain MBR was not well demonstrated, the TEM studies revealed that the final microbial pathway of Ni(II) reduction was intracellularly localized. Since the earlier studies of electron transfer in Geobacter species and Shewanella putrefaciens MR-1 Lovley et al 1993;Myers and Myers 2001), cytochromes involvement in electron transfer to Ni(II) has been speculated. Further studies on the potential role of external membrane proteins in electron transfer to Ni(II) by strain MBR are needed.…”
Section: Discussionmentioning
confidence: 99%